2010
DOI: 10.1021/jf101555d
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Fermentation Performance of Grain Sorghums (Sorghum bicolor) with Modified Endosperm Matrices

Abstract: We tested 13 sorghum entries (lines and hybrids) with different endosperm matrices for ethanol production using a laboratory dry grind process. Waxy and heterowaxy samples had the highest efficiencies. Free amino nitrogen (FAN) contents in sorghum samples were positively related to the fermentation rate during fermentation (R2=0.8618). Dried distiller's grain with solubles (DDGS) from different sorghums had significantly different crude protein and crude fat contents. Residual starch content in DDGS ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 35 publications
9
28
0
Order By: Relevance
“…In a work reported by Wang et al (2008), nine sorghum genotypes were selected and used to study the effect of protein availability on efficiency of ethanol fermentation. The results showed a strong positive linear relationship between protein digestibility and fermentation efficiency, indicating the influence, and at the same time, the usefulness of this sorghum grain features as predictor of ethanol yield (Rooney et al, 2007;Wang et al, 2008;Wu et al, 2007;Wu et al, 2010a). In Fig.…”
Section: Conventional Dry Grindmentioning
confidence: 92%
See 2 more Smart Citations
“…In a work reported by Wang et al (2008), nine sorghum genotypes were selected and used to study the effect of protein availability on efficiency of ethanol fermentation. The results showed a strong positive linear relationship between protein digestibility and fermentation efficiency, indicating the influence, and at the same time, the usefulness of this sorghum grain features as predictor of ethanol yield (Rooney et al, 2007;Wang et al, 2008;Wu et al, 2007;Wu et al, 2010a). In Fig.…”
Section: Conventional Dry Grindmentioning
confidence: 92%
“…Waxy starches are thereby easily gelatinized and hydrolyzed, giving high conversion efficiencies (Wu et al, 2007). Thus, the waxy characteristics improved the susceptibility of the endosperm matrix for low-energy gelatinization, enzymatic hydrolysis and total ethanol production (Wu et al, 2010a). In the case of proteins, Wu et al (2010a) indicate that high-lysine, high-protein-digestibility (HD) sorghum lines have been developed.…”
Section: Use Of Biotechnology To Improve Ethanol Yields 521 Geneticmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a comparison of normal, high digestibility, waxy and waxy-high digestibility lines, some of the latter were among the best yielding, suggesting that it is possible to breed agronomically acceptable cultivars (Jambala et al, 2012). They also show promise for bioethanol production, having easily pasted starch granules, yielding higher free amino nitrogen, giving faster fermentation and producing lysine-rich distillers dry gain and solubles (DDGS), compared to normal sorghum lines (Wu et al, 2010).…”
Section: The Africa Biofortified Sorghum (Abs) Project Led By the Afmentioning
confidence: 99%
“…Other work indicated that waxy sorghum adjunct gave higher extract yield, filtered more rapidly than normal sorghum and produced a wort with the same level of fermentable carbohydrates (Osoria-Morales et al, 2000). Similarly, a study of the effect of sorghum endosperm type on bioethanol production showed that waxy and heteroxy waxy lines had the highest efficiency (Wu et al, 2010).…”
Section: Macronutrients Starchmentioning
confidence: 99%